Electric vehicles and energy-saving technologies – master's degree program under the Erasmus project Cybphys - Hnatov, Andrii; Arhun, Shchasiana; Гнатов, Андрій Вікторович; Аргун, Щасяна Валіковна (Харківський національний автомобільно-дорожній університет, 2022)
Problem. The quality of higher education is achieved by compliance with the conditions for the implementation of educational activities and learning outcomes with the requirements of legislation and higher education standards, professional and international standards, as well as the needs of stakeholders and society. Obviously, the requirements, recommendations and opinions of stakeholders play one of the main roles in the process of ensuring the quality of higher education. It should be noted that without ensuring and improving the quality of higher education, it is impossible to obtain accreditation of an educational program (EP) in the relevant specialty. Goal. Analysis and processing of feedback received from employers and representatives of the academic community who have experience in working and teaching in the 141 specialty "Electric Power Engineering, Electrical Engineering and Electromechanics" to improve the quality of education under the master's EP "Electric vehicles and energy-saving technologies". Methodology. The method of questioning consists in obtaining information by means of written answers of respondents to a system of standardized questions. Methods of information processing and synthesis method - the study of an object in its integrity, in the unity and interconnection of its parts. Results. An analytical review of decisions on EP and publications on the introduction of innovative teaching methods and methods of maintaining the quality of the educational process into the educational process was carried out. In a number of educational components, the list of literature will be expanded due to the technical documentation of automakers and references to modern research by foreign authors. It is proposed to improve the existing and develop new laboratory and practical work on modern equipment purchased through the «CybPhys» project and on the equipment of interested employers. It is proposed to expand the practice of the educational components of the EP related to the cycle of professional training disciplines. It is proposed to add the topic "Alternative power sources" to the cycle of disciplines of the applicant's free choice (professional training section). Originality. It is proposed to conduct practical and laboratory classes and conduct research on the topic of the thesis directly in production and in the daily work of service stations and car service. Practical value. Based on the results of the feedback received from stakeholders, appropriate changes will be made to the courses that will improve the quality of education and make the master's EP "Electric vehicles and energy-saving technologies" even more relevant and actual for the labor market in the field of electric power, electrical engineering and electromechanics, in particular, with regard to the industry electric vehicles and energy saving technologies.
Електромобілі та енергозберігаючі технології – магістерська освітня програма за Еразмус проєктом Cybphys
Keywords: energy-efficient technologies; master's program; educational program; energy-saving technologies; grant project; electrical engineering and electromechanics; quality of higher education; stakeholder; енергоефективні технології; магістерська програма; освітня програма; енергозберігаючі технології; грантовий проект; електротехніка та електромеханіка; якість вищої освіти; стейкхолдер; 378.14; 10.30977/AT.2019-8342.2022.51.09